Influence of blood trace elements on immune responses and adverse symptoms subsequent to Sinopharm COVID-19 vaccination - Abbasifard, Mitra; Kazerooni, Kooros; Taghipour Khaje Sharifi, Gholamhossein; Bagheri-Hosseinabadi, Zahra; Hajizadeh, Mohammad Reza (Scientific reports, 2024)
Trace elements, specifically magnesium (Mg), zinc (Zn), and selenium (Se) have been linked with immunomodulatory properties. This research delves into identifying the potential impression of serum levels Mg, Zn, and Se on the protective immunity arisen through Sinopharm COVID-19 vaccine in the vaccinated subjects. Levels of Mg, Zn, and Se, cytokine and antibody production as well as virus neutralization potency were investigated in 75 males and 75 females before and 2 weeks after first and second dose of vaccination. Level of Mg, Zn, and Se did not change significantly before and 2 weeks after first and second dose of vaccine administration. Concentrations of Interleukin (IL)-2, IL-6, and Interferon (IFN)-γ were significantly higher in the supernatant of peripheral blood mononuclear cells (PBMCs) obtained from subjects 2 weeks after both first and second dose of vaccination compared to before vaccination. Serum level IgG was significantly higher 2 weeks after first and second dose of vaccination compared to before vaccination. Serum level IgM was only higher after first dose of vaccination compared with before vaccine. Also, 2 weeks after both first and second dose of vaccination compared to before vaccination, FRNT 50 titer was significantly higher. Levels of Mg, Zn, and Se did not significantly correlate with levels of IL-2, IL-6, IFN-γ, IgM and IgG, and FRNT 50 after first and second dose of vaccination. No severe unwanted clinical symptoms were detected after vaccination. Mg, Zn, and Se do not play a role in modulating protective immunity during Sinopharm COVID-19 vaccine.